Pelatihan Konseling Traumatis untuk Membantu Korban Bullying di SMA Kota Surabaya: Traumatic Counseling Training to Help Victims of Bullying in Senior High Schools in Surabaya - Nursalim, Mochamad (Amalee: Indonesian Journal of Community Research and Engagement, 2022)
The phenomenon of the number of bullying occurring in schools, needs serious attention. The results of the interview show that many counselors in high school do not know how to handle bullying victims who experience PTSD (Post Traumatic Stress Disorder). For this reason, counseling training for BK teachers is needed. The purpose of this community service is to increase the ability of high school counseling teachers in Surabaya in reducing PTSD triggered by bullying events by using traumatic counseling. The PKM method used is training with the steps of presenting the material, modeling, simulation, practice, and giving structured assignments. The number of participants in this PKM activity was 20 BK teachers at the Surabaya City High School. The results of the PKM implementation show that: the absorption capacity of PKM participants exceeds or is above the required minimum score. 2) Changes in participants' behavior in the affective aspect can be seen in changes in perceptions and attitudes that are getting better towards the training and show feelings of pleasure and interest and want to learn more about Traumatic Counseling. 3) Changes in participants' psychomotor abilities can be seen from the mastery of techniques and skills, namely the skills to identify PTSD. The score of counseling practice is 89. Based on the discussion, it can be concluded that there is an increase in the mastery of Traumatic Counseling training material, a change in perception and attitude that is getting better and there is a mastery of techniques and skills to identify PTSD as well as an increase in the score of the practice of traumatic counseling.